INTERTEKSTUALITAS NOVEL SUTRA SOMA BAHTERA NUSANTARA KARYA MOCH. INDRA PURNAMA DAN DHAENG SEKARA TELIK SANDI TANAH PELIK MAJAPAHIT KARYA AGUS SUNYOTO - Tri Agung Bayu Ambarsari; Eggy Fajar Andalas (STKIP Siliwangi, 2021)
Literature doesn’t exist in vacuum. This is because literary workd are always related to the text of their predecessors. Therefore, this study aims to describe the intertextuality between Sutra Soma Bahtera Nusantara (2019) and Dhaeng Sekara Telik Sandi Tanah Pelik Majapahit (2010). This type of research is qualitative. The data collection technique was carried out using the note-taking technique. Data analysis was performed with the stages of data reduction, presentation of results, and drawing conclusions. The results showed and intertextuality relationship between the two novels. This relationship reflected in the intrinsic elemental relationship described in the two novels. The novel Dhaeng Sekara Telik Sandi Tanah Pelik Majapahit is a hipogram of the Sutra Soma Bahtera Nusantara novel as its transformation text